INVESTIGATION OF BALL BEARING ROLLING ELEMENT DEFECT BY THE VIBRATION ANALYSIS METHOD - Hakan ARSLAN (Pamukkale University Journal of Engineering Sciences, 2007)
In this study, a local surface defect in radial ball bearings is studied by analytical and experimental methods using the vibration analysis method. For this purpose, an artificial local defect on the running surface of the rolling element is made and resulting radial shaft vibrations are recorded. For the analytical investigation, a theoretical model for this system is also established and a simulation program is developed for local defects and defect-free bearings. Simulation results are obtained for the same shaft and bearing dimensions used in the experimental set and vibration spectra for different shaft speeds are obtained. When the vibration spectrums obtained analytically are compared with the ones obtained experimentally, similar results have been in both cases.